2023
DOI: 10.1177/19458924231193526
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Epigenetic Study of Chronic Rhinosinusitis Tissues Reveals Dysregulated Inflammatory, Immunologic and Remodeling Pathways

Abstract: Background Epigenetics studies mechanisms such as DNA methylation, histone modifications, non-coding RNAs, and alternative polyadenylation that can modify gene activity without changing the underlying DNA nucleotide base-pair structure. Because these changes are reversible, they have potential in developing novel therapeutics. Currently, seven pharmaceutical agents targeting epigenetic changes are FDA approved and commercially available for treatment of certain cancers. However, studies investigating epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Previous genetic and epigenetic studies have implicated TNF alpha, showing higher levels in CRSwNP 9 . Other top URs include LPS (pro‐inflammatory toxin on the outer membrane of gram‐negative bacteria, activates TLR4 inflammation) and beta‐estradiol (a sex hormone) both of which were identified in our previous study 2 . Overall, the results greatly overlap with our previous DNA methylation study which used ITM for control 2 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previous genetic and epigenetic studies have implicated TNF alpha, showing higher levels in CRSwNP 9 . Other top URs include LPS (pro‐inflammatory toxin on the outer membrane of gram‐negative bacteria, activates TLR4 inflammation) and beta‐estradiol (a sex hormone) both of which were identified in our previous study 2 . Overall, the results greatly overlap with our previous DNA methylation study which used ITM for control 2 …”
Section: Discussionsupporting
confidence: 76%
“…TNF was another top UR in CRS/CRSwNP versus controls 2 . Previous genetic and epigenetic studies have implicated TNF alpha, showing higher levels in CRSwNP 9 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As research uncovers more about the nuances of Chronic Rhinosinusitis (CRS), more questions inevitably arise, and with that multitudes of opportunities for potential novel treatments. One such attempt to do so was undertaken by Brar et al 1 to understand and delineate the effects of epigenetics and environmentally induced pathogenic changes and its impact on CRS patients. In this study, several upstream regulators and pathways were identified as potential targets for CRS treatment.…”
mentioning
confidence: 99%